Transformasi Branding UMKM Melalui Digital Marketing Dalam Meningkatkan Pemasaran Pada Pasar Wisata Harmoni Keputih - Muhammad Maulana Ramadhan; Siti Ning Farida (Yayasan Daarul Huda Kruengmane, 2023)
Nowadays, the role of Micro, Small, and Medium Enterprises (MSMEs) as drivers of Indonesia's economic growth is significantly influential. The strength of branding in good products and effective strategies may fail if they lack good branding quality, which can have negative impacts on product marketing. Customer satisfaction also plays a crucial role in the product's market value. In this research, we focused on MSMEs predominantly located in the Harmoni Keputih Tourism Market in Surabaya City, while also assisting some MSMEs in the Keputih Subdistrict. The community engagement activities were conducted using a qualitative approach involving observation, documentation, and interviews with the MSME owners regarding the challenges they face in marketing their products. Based on the results of the survey and interviews conducted, there are still MSMEs that continue to use conventional marketing methods and lag behind compared to other MSMEs in the Keputih Subdistrict, although their number is not significant. In the era of Industry 4.0, like the present, Digital Marketing can have both positive and negative impacts on the sales and revenue of MSMEs. Therefore, MSMEs need to adopt strong branding transformation to differentiate themselves in the market and attract consumers. In this regard, digital marketing becomes the primary and effective tool to enhance the marketing of MSMEs in that market. By employing the right digital marketing strategies, UMKM can reach a broader audience through social media, websites, and online advertisements.